2019
DOI: 10.1007/s11783-019-1122-7
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of antibiotic resistance genes and control of horizontal transfer risk by UV-based treatment of drinking water: A mini review

Abstract: Antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARGs) have been recognized as one of the biggest public health issues of the 21st century. Both ARB and ARGs have been determined in water after treatment with conventional disinfectants. Ultraviolet (UV) technology has been seen growth in application to disinfect the water. However, UV method alone is not adequate to degrade ARGs in water. Researchers are investigating the combination of UV with other oxidants (chlorine, hydrogen peroxide (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(28 citation statements)
references
References 80 publications
0
28
0
Order By: Relevance
“…Subsequently, bacteria that contain resistant genes are not effectively eliminated and sometimes even increase inside the biological components of WWTPs (Ben et al 2017;Zanotto et al 2016). Although disinfection processes are vital to advance effluent biosecurity, disinfection with chlorine or ultraviolet light cannot guarantee the removal of antimicrobial resistant genes (Sharma et al 2019). Consequently, there is a risk that antimicrobial resistance is being distributed by discharge or reuse of WWTP effluents in receiving environments, such as rivers and wastewater-irrigated soils (Ben et al 2017;Makowska et al 2016).…”
Section: Case 2: Wastewater Reusementioning
confidence: 99%
“…Subsequently, bacteria that contain resistant genes are not effectively eliminated and sometimes even increase inside the biological components of WWTPs (Ben et al 2017;Zanotto et al 2016). Although disinfection processes are vital to advance effluent biosecurity, disinfection with chlorine or ultraviolet light cannot guarantee the removal of antimicrobial resistant genes (Sharma et al 2019). Consequently, there is a risk that antimicrobial resistance is being distributed by discharge or reuse of WWTP effluents in receiving environments, such as rivers and wastewater-irrigated soils (Ben et al 2017;Makowska et al 2016).…”
Section: Case 2: Wastewater Reusementioning
confidence: 99%
“…Extant previous studies have already revealed the prevalence of ARB and ARGs and their removal efficiencies through the physical, biological and chemical treatment processes in WWTPs (Chen and Zhang, 2013;Wang et al, 2018a;Sharma et al, 2019;Li et al, 2020). However, understanding the behavior of ARGs and viruses is very limited in small-scaled and decentralized sewage treatment facilities.…”
Section: H I G H L I G H T Smentioning
confidence: 99%
“…Currently, there are already published several reviews that summarize the treatment strategies comprehensively to combat antibiotic resistance in WWTPs, which represent one of the major places where antibiotic resistance evolves [13,14,30,64,65]. To reduce the environmental and health impact of ARB and ARGs, it is vital to understand the efficiency and mechanism of the treatment technologies and the limitations for their eventual application.…”
Section: Technologies To Abate Microbial Resistancementioning
confidence: 99%
“…These methods still offer a challenge to researchers in the field. Some publications have shown that ARB can be effectively removed under laboratory conditions by chlorination or UV [122], and up to 100% if chlorination and UV are combined as a treatment process [56,65]; moreover, the UV irradiation and low-level chlorine treatment reduced the gene transfer frequency by conjugation mechanisms [121], and ARGs genes can also be removed to different extents [56,74,121,123]. The reduction of ARGs (blaVIM, vanA, ampC, and ermB) ranged from 18.7% to up to 99.3% for ozonation.…”
Section: Disinfection Treatmentsmentioning
confidence: 99%